Female entrepreneurship in Singapore. - Seah, Samantha Xiaoli. (2008)
The purpose of our study is to investigate factors leading to a less conducive entrepreneurial environment amongst the female gender in Singapore. Enterprising Singaporeans is one the key determinants in ensuring Singapore's long term competitiveness. We undertook a survey and interview approach to gather our findings.